Safety and Outcomes of Intravenous Thrombolysis in Posterior Versus Anterior Circulation Stroke: Results From the Safe Implementation of Treatments in Stroke Registry and Meta-Analysis - Keselman, Boris; Gdovinová, Zuzana; Jatuzis, Dalius; Melo, Teresa Pinho E; Vilionskis, Aleksandras; Cavallo, Roberto; Frol, Senta; Jurak, Lubomir; Koyuncu, Bahar; Nunes, Ana Paiva; Petrone, Alfredo; Lees, Kennedy R; et al. (Stroke, 2020)
Background and Purpose- Posterior circulation stroke (PCS) accounts for 5% to 19% of patients with acute stroke receiving intravenous thrombolysis. We aimed to compare safety and outcomes following intravenous thrombolysis between patients with PCS and anterior circulation stroke (ACS) and incorporate the results in a meta-analysis. Methods- We included patients in the Safe Implementation of Treatments in Stroke Thrombolysis Registry 2013 to 2017 with computed tomography/magnetic resonance angiographic occlusion data. Outcomes were parenchymal hematoma, symptomatic intracerebral hemorrhage (SICH) per SITS-MOST (Safe Implementation of Thrombolysis in Stroke Monitoring Study), ECASS II (Second European Co-operative Stroke Study) and NINDS (Neurological Disorders and Stroke definition), 3-month modified Rankin Scale score, and death. Adjustment for SICH risk factors (age, sex, National Institutes of Health Stroke Scale, blood pressure, glucose, and atrial fibrillation) and center was done using inverse probability treatment weighting, after which an average treatment effect (ATE) was calculated. Meta-analysis of 13 studies comparing outcomes in PCS versus ACS after intravenous thrombolysis was conducted. Results- Of 5146 patients, 753 had PCS (14.6%). Patients with PCS had lower median National Institutes of Health Stroke Scale: 7 (interquartile range, 4-13) versus 13 (7-18), P<0.001 and fewer cerebrovascular risk factors. In patients with PCS versus ACS, parenchymal hematoma occurred in 3.2% versus 7.9%, ATE (95% CI): -4.7% (-6.3% to 3.0%); SICH SITS-MOST in 0.6% versus 1.9%, ATE: -1.4% (-2.2% to -0.7%); SICH NINDS in 3.1% versus 7.8%, ATE: -3.0% (-6.3% to 0.3%); SICH ECASS II in 1.8% versus 5.4%, ATE: -2.3% (-5.3% to 0.7%). In PCS versus ACS, 3-month outcomes (70% data availability) were death 18.5% versus 20.5%, ATE: 6.0% (0.7%-11.4%); modified Rankin Scale score 0-1, 45.2% versus 37.5%, ATE: 1.7% (-6.6% to 3.2%); modified Rankin Scale score 0-2, 61.3% versus 49.4%, ATE: 2.4% (3.1%-7.9%). Meta-analysis showed relative risk for SICH in PCS versus ACS being 0.49 (95% CI, 0.32-0.75). Conclusions- The risk of bleeding complications after intravenous thrombolysis in PCS was half that of ACS, with similar functional outcomes and higher risk of death, acknowledging limitations of the National Institutes of Health Stroke Scale for stroke severity or infarct size adjustment.
Keywords: trombolytická terapie; acute stroke; Male; anterior circulation brain infarction; cerebrální krvácení; Risk Factors; tissue-type plasminogen activator; cerebral hemorrhage; cévní mozková příhoda; Stroke; Aged; mužské pohlaví; senioři; Thrombolytic Therapy; senioři nad 80 let; lidé; ženské pohlaví; systematic review; Humans; rizikové faktory; Aged, 80 and over; meta-analysis; Cerebral Hemorrhage; Female; lidé středního věku; posterior circulation brain infarction; Middle Aged